Meningkatan Aktivitas, Keterampilan Berbicara, dan Hasil Belajar Menggunakan Model Prolog pada Kelas IV Sekolah Dasar - Fitri Handayani; Dessy Dwitalia Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
The problems that occur are low activity, speaking skills, and learning outcomes in Indonesian language content. The aim of this research is to describe educators' activities, analyze students' activities, speaking skills and learning outcomes. The approach used is qualitative with the PTK type of research carried out in 4 meetings and the subjects studied were class IV students at SDN Antar Baru 1 Marabahan. The results of this research show that the teacher's activities received a score of 100 with the criteria